Joshua $1 (BCompletes - Ebers, Georg, 1837-1898; Safford, Mary J. (Mary Joanna), 1842-1916 (Salt Lake City, UT : Project Gutenberg, 2004)
"Joshua $1 (BComplete" by Georg Ebers is a historical novel written in the late 19th century. The narrative is set during the time of the Exodus of the Hebrews from Egypt and focuses on the character of Joshua, examining the emotional and spiritual journeys faced by the Hebrew people as they seek freedom from oppression and fulfill their divine destiny. The novel weaves biblical events with rich character development, emphasizing the human experience during one of history's most significant migrations. At the start of the novel, readers are introduced to poignant scenes of impending doom as an old astrologer and his grandson witness ominous signs in the night sky, foretelling calamity for the Egyptians. The fears of plague and despair grip Tanis, the city they inhabit. The astrologer grieves not just for his people, but for the loss of his family, as news of deaths from the plague devastates them. The chaos culminates in an uprising against the Hebrews as Egyptians react to the calamity by turning against the people they see as responsible. The opening establishes a tense atmosphere filled with foreboding, portraying the depths of human anguish and the intersection of fate, divine will, and historical events in the context of a transformative journey marked by faith and loss. (This is an automatically generated summary.)s
Release date is 2004-11-15
Produced by David Widger
Keywords: Palestine -- History -- Fiction; German fiction -- Translations into English